Prevalence of common bacterial STI pathogens and the microscopic diagnostic approach to abnormal vaginal discharge in a tertiary care hospital in Bangkok, Thailand - Chenchit Pichailuck; Piyachat Sakunborrirak; Rossaphorn Kittiyaowamarn; Chanon Neungton; Pareeda Taunwaena; Natnaree Girdthep; Rungnapa Luengprasit; Pochamana Phisalprapa; Chayanis Kositamongkol (PLoS ONE, 2025)
In Thailand, sexually transmitted infections (STIs) persist as a significant public health issue, notwithstanding the affordability of treatments. The primary challenge lies in diagnostic methodologies. According to the Thai National Treatment Guidelines for abnormal vaginal discharge, wet preparation using proportion of white blood cell (WBC) counts and epithelial cell (EC) guides presumptive STI treatment. This study investigated the prevalence of common STI pathogens in sexually active women presenting with abnormal vaginal discharge and WBC > EC under microscopy; and the cost-minimization analysis of this approach. A cross-sectional study was done during July 2021–March 2023 at the Siriraj Female STI Clinic, Bangkok, Thailand. The eligible participants were non-pregnant Thai women aged 18–50 years with the following conditions; being sexually active in prior one year, presenting with abnormal vaginal discharge, having WBC > EC under microscopy, and no allergy to cefixime and azithromycin which were the presumptive treatment in the study. The endocervical swabs were sent for molecular diagnosis of STI pathogens (polymerase chain reaction; PCR). Cost-minimization analysis comparing two approaches, PCR and wet preparation, was done. From an initial 199 participants, 186 were eligible. The average age was 31.1 ± 9.4 years and their sex debut was at 19.7 ± 3.8 years. Around 10% of them, sex partners had STIs. Prevalent STI pathogens included C. trachomatis(20.4%), N. gonorrhoeae(7.0%), M. genitalium(5.9%) and T. vaginalis(3.8%). Presumptive treatment yielded no severe immediate or delayed adverse effects. Using wet preparation as a primary test with presumptive treatment, cost per one case cured was almost three times lower than that of using PCR as a primary test (1250.0 vs 3454.4 Thai Baht). In summary, a quarter of the sexually-active Thai women with abnormal vaginal discharge and WBC > EC under microscopy had either C. trachomatis or N. gonorrhoeae. The use of wet preparation-guided presumptive STI treatment is practical and cost-saving, compared with the PCR approach. Trial registration: Thai Clinical Trial Registry (TCTR20210702001, 2 July 2021).